Effects of hypertonic saline, alternate day and daily rhDNase on healthcare use, costs and outcomes in children with cystic fibrosis. Issue 10 (1st October 2002) - Suri, R; Grieve, R; Normand, C; Metcalfe, C; Thompson, S; Wallis, C; Bush, A
Abstract : Background: Daily recombinant human deoxyribonuclease (rhDNase) is an established but expensive treatment in cystic fibrosis (CF). An alternative lower cost therapy is hypertonic saline (HS), which has been shown to improve lung function in short term studies. This study compares the costs and consequences of daily rhDNase with alternate day rhDNase and HS in children with CF. Methods: In an open, randomised, crossover trial, 48 children with CF were allocated consecutively to 12 weeks of once daily 2.5 mg rhDNase, alternate day 2.5 mg rhDNase, and twice daily 5 ml 7% HS. Outcomes assessed included forced expiratory volume in 1 second (FEV1 ) and quality of life. All healthcare resource use was prospectively recorded for each patient. Unit costs were collected and combined with resource use data to give the total health service costs per patient for each treatment strategy. Results: Daily rhDNase resulted in a significantly greater increase in mean FEV1 than HS (8%, 95% CI 2 to 14) but there was no significant difference in FEV1 between daily and alternate day rhDNase (2%, 95% CI –4 to 9). Over a 12 week period the mean incremental costs of daily rhDNase compared with HS was £1409 (95% CI £440 to £2318), and the incremental cost of using daily rather than alternate day rhDNase was £513 (95% CI –£546 to £1510). Conclusions: Daily rhDNase is more effective than 5 ml 7% HS twice daily delivered by jet nebuliser, but significantly increases healthcare costs. Administering rhDNase on an alternate day rather than a daily basis is as effective, with a potential for cost savings.